Chemical characterization of non-volatile dissolved organic matter from oilfield-produced brines in the Nanyishan area of the western Qaidam Basin, China. (April 2021) - Zhang, Yaoling; Yang, Keli; Dong, Yaping; Nie, Zhen; Li, Wu
Abstract: Oil and gas (O&G) produced water (PW) is the largest waste stream generated in oil and gas industries. A comprehensive understanding of the compositions and features of dissolved organic matter (DOM) in O&G PWs from different geologic formation, ages, and origins is crucial for controlling their adverse effects and developing efficient technologies for treatment and reuse. In this study, four non-volatile DOM samples were isolated from oilfield-produced brines in the Nanyishan area of the Qaidam Basin and characterized by a multi-analytical approach. Results indicated that the compositions of the studied DOM samples were dominated by aliphatics, which may originate from shale-derived oil hydrocarbons as well as plants, algae, and bacteria from lacustrine deposits. Smaller amounts of cyclic aliphatic compounds were also identified in the DOM samples. Samples contained relatively low concentrations of carbohydrates that probably related to microbes in the oilfield brines. Concentrations of polycyclic aromatic hydrocarbons and aromatics were also low, likely due to limited influence from petroleum oil and/or organic chemicals added to the oilfield brines. The contents of nitrogen- and sulfur-containing heterocyclic compounds were all very low and could have been partly influenced by inorganic compositions of the brines. Moreover, the abundance of unsubstituted aliphatics and halogen-containing compounds may be potential indicators of the age and/or the type of oil/gas wells. Results from this study can further our knowledge of the structures and compositions of oilfield PW DOM samples originating from continental sources. Graphical abstract: Image 1 Highlights: DOM isolated from oilfield-produced brines were well characterized. Unsubstituted and substituted aliphatics were the dominant DOM compositions. The contents of carbohydrates and aromatics were relatively lower. The contents of nitrogen- and sulfur-containing compounds were all very low.